Phase Stability and Solidification of 9Cr-ODS Alloys for Wire Additive Manufacturing: A Computational Approach - Sarah Najm Al-Challabi; Ali Samer Muhsan; Thar Mohammed Badri; Mohammad Shakir Nasif (Results in Engineering)
The increasing demand for advanced materials capable of withstanding high-temperature and harsh environments, such as those utilized in nuclear reactors and aerospace applications, has driven significant interest in Oxide Dispersion Strengthened (ODS) alloys. While these materials offer remarkable thermomechanical properties, challenges remain in optimizing their phase stability and microstructural evolution during additive manufacturing processes such as Wire Arc Additive Manufacturing (WAAM) and Plasma Additive Manufacturing (PAM). This study addresses the gaps in the literature regarding the impact of processing parameters (temperature and scanning speed) nickel (Ni) content on the phase stability of 9Cr-ODS alloys. Using computational thermodynamics tools, including CALPHAD, the Scheil-Gulliver model, and DICTRA simulations, this study evaluates the effects of temperature (1480-1550°C), scanning speed (0.1 - 0.2 m/s), and Ni content (0.27-8%) on the formation of FCC, BCC, and carbide (M7C3) phases. Elemental distribution analysis across a 100 µm region confirms a stable FCC_L12 phase composition (100%) with no detectable M7C3_D101 phase. Thermal property analysis indicates a liquidus temperature range of 1470.27°C to 1500.67°C and a solidus temperature range of 1387.91°C to 1462.38°C, with thermal conductivity varying between 23.05 W/m·K and 27.56 W/m·K. Phase composition studies using the Scheil model reveal that at 1480°C, the FCC_L12 phase comprises 65% of the solidified structure, decreasing to 55% at 1500°C and further reducing to 45% at 1550°C, where BCC_B2 becomes dominant at 55%. These insights highlight the importance of precise control over processing parameters to optimize the mechanical and thermal performance of 9Cr-ODS alloys. The study underscores the utility of computational tools in predicting phase transformations, reducing experimental iterations, and guiding process optimization. Future research should explore advanced cooling techniques, broader parameter ranges, and the long-term stability of these alloys under cyclic thermal and mechanical loads to support their application in demanding industries like nuclear energy and aerospace.